The historical and literary value of Algerian travel writing during the Ottoman period - roubache, imane (El Omda in Linguistics and Discourse Analysis, 2025)
The Algerian trips during the Ottoman era, especially the "Hijaz trip, and specifically the Warthlan trip", have two great values: a historical scientific value and a literary one. The artistic mechanisms used by the traveler to reproduce the events and facts that he lived in on the ground, and thus the Algerian nomadic text in the Ottoman era was able to achieve for the reader pleasure and benefit at the same time.